Kilka przykładów.

a) 5n² - 2n - 4n² + 40n/8 =
b) 8m² - 10/2 - 20m² + 15/5 =
c) 3x² + 4 + 1/7 * 14x² - 21/6 =
d) 15p² - 9p/6 - 6 * 1 - 6p/4 =
e) (2a + b) * c - (2ac - bc + 1) =
f) 6(a² + b + ⅓) - (a² - ½) - 3(b + ⅓) =

Z góry dzięki.

2

Odpowiedzi

2009-11-22T19:44:07+01:00
A) 5n² - 2n - 4n² + 40n/8 = 1n²-2n+5n = n²+3n
b) 8m² - 10/2 - 20m² + 15/5 = -12m²-5+3 = -12m²-2
c) 3x² + 4 + 1/7 * 14x² - 21/6 =3x²+4+2x²-3 ½=5x²+½
d) 15p² - 9p/6 - 6 * 1 - 6p/4 =15p²-1,5p-6-1,5p=15p²-3p-6
e) (2a + b) * c - (2ac - bc + 1) = 2ac+bc-2ac+bc-1=2bc-1
f) 6(a² + b + ⅓) - (a² - ½) - 3(b + ⅓) = 6a²+6b+2-a²+0,5-3b-1 =
5a²+3b+1,5
2009-11-22T19:51:16+01:00
A) 5n²-2n-4n²+40n÷8=
=n²-2n+5n=n²+3n
b)8m²-10÷2-20m²+15÷5=
=-12m²-5+3=-12m²-2
c)3x²+4+1÷7×14x²-21÷6=
=3x²+4+2x²-3½=
=5x²+½
d)15p²-9p÷6-6×1-6p÷4=
=15p²-18p÷12-6-18p÷12=
=15p²-3p-6
e) (2a+b)×c-(2ac-bc+1)=
2ac+bc-2ac+bc-1=
=2bc-1
f)6(a²+b+⅓)-(a²-½)-3(b+⅓)=
=6a²+6b+2-a²+½-3b-1=
=5a²+3b+1